Analysis of a severe head injury in World Cup alpine skiing - Yamazaki, J.; Gilgien, M.; Kleiven, S.; Mcintosh, A. S.; Nachbauer, W.; Müller, E.; bere, T.; Bahr, R.; Krosshaug, T. (Medicine & Science in Sports & Exercise, 2015)
Traumatic brain injury (TBI) is the leading cause of death in alpine skiing. It has been found that helmet use can reduce the incidence of head injuries between 15% and 60%. However, knowledge on optimal helmet performance criteria in World Cup alpine skiing is currently limited owing to the lack of biomechanical data from real crash situations.